PENGAWASAN BADAN PERMUSYAWARATAN NAGARI (BAMUS) TERHADAP WALI NAGARI DALAM PENYELENGGARAAN PEMERINTAHAN NAGARI MUARA SAKAI - Nur Afifah Agusma Yeni; Hasbullah Malau (Politeknik STIA LAN Makassar, 2021)
Nagari Government is the administration of government affairs and the interests of the Nagari people in the system of Government of the Unitary State of the Republic of Indonesia. Wali Nagari as government administrators and BAMUS (Consultative Body) as supervisory institutions. The problem that occurs in Nagari Muara Sakai is that BAMUS supervision of the Wali Nagari Muara Sakai is not carried out thoroughly. There are several activities that are not supervised by BAMUS. This is caused by several factors that become obstacles for BAMUS in conducting supervision. This study was conducted to analyze the supervision carried out by BAMUS Nagari against Wali Nagari in the administration of the Muara Sakai Nagari Government and to find the inhibiting factors of this supervision. This study uses descriptive qualitative research methods, describing events or phenomena according to what is happening in the field. This research was conducted in Nagari Muara Sakai, Pancung Soal District, Pesisir Selatan Regency, West Sumatera. The data and information found in the field are analyzed using direct and indirect supervision theory. The result of this research is that BAMUS Nagari's supervision of the Wali Nagari Muara Sakai is carried out through village consultations, verbal communication, BAMUS goes directly to the field, through coordination, written reports, monitoring, and evaluation. However, the supervision carried out by BAMUS has not gone well. There are several factors that hinder BAMUS's supervision of the Wali Nagari Muara Sakai, namely poor communication between BAMUS and Wali Nagari, asynchronous actions between BAMUS and Wali Nagari in several activities, the lack of BAMUS ideas in carrying out the supervisory function, and the lack of transparency of the Nagari Wali regarding several activities. Nagari.